2015
DOI: 10.1186/s12889-015-2078-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing full immunization coverage among 12–23 months of age children in Ethiopia: evidence from the national demographic and health survey in 2011

Abstract: BackgroundImmunization remains one of the most important public health interventions to reduce child morbidity and mortality. The 2011 national demographic and health survey (DHS) indicated low full immunization coverage among children aged 12–23 months in Ethiopia. Factors contributing to the low coverage of immunization have been poorly understood. The aim of this study was to identify factors associated with full immunization coverage among children aged 12–23 months in Ethiopia.MethodsThis study used the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
198
10
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(261 citation statements)
references
References 33 publications
(31 reference statements)
48
198
10
5
Order By: Relevance
“…Further, older maternal and child's age and lower distance from the immunization centre among others were found to be strongly linked with the likelihood of increased influenza vaccination up take for children in Kenya (Otieno et al, 2014). Also belonging in the rich index by mother was found by Lakew et al (2015) to be one of the determinants of full immunization of children in Ethiopia. On Ghana, it has been found that children membership of National Health Insurance Scheme (NHIS), mother's education and geographical location determined full immunization of children (Dwumoh et al (2014).…”
Section: Review Of Literaturementioning
confidence: 93%
“…Further, older maternal and child's age and lower distance from the immunization centre among others were found to be strongly linked with the likelihood of increased influenza vaccination up take for children in Kenya (Otieno et al, 2014). Also belonging in the rich index by mother was found by Lakew et al (2015) to be one of the determinants of full immunization of children in Ethiopia. On Ghana, it has been found that children membership of National Health Insurance Scheme (NHIS), mother's education and geographical location determined full immunization of children (Dwumoh et al (2014).…”
Section: Review Of Literaturementioning
confidence: 93%
“…On the empirical front with regards to the determinants of immunization or vaccine utilization, Russo et al (2015) found in Dschang of Cameroon that, less usage of antenatal care by mothers, immunization card retention, child being the third or beyond with regards to birth order, younger mother's age, poor parental information on vaccination as well as poor parental attitude towards immunization are the major factors affecting incomplete immunization among children aged 12-23 months. Lakew et al (2015) found that, mother being in the rich wealth index, mothers being aware of community conversation programme, getting postnatal check-up within 2 months after birth, and sources of information from vaccination cards were the determinants of full immunization among children aged 12-23 months in Ethiopia. Cockcroft et al (2014) found in Nigeria that mothers education, having birth certificates, discussion of immunization at home and mother's thinking of immunization as important were associated with the probability that a child aged 12-23 months received measles vaccination.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Thus with regards to the pneumococcal and rotavirus vaccines, children in Ghana are expected to receive all the three doses of the pneumococcal vaccine (pneumococcal 1, pneumococcal 2 and pneumococcal 3 vaccines) as well as all the two doses of the rotavirus vaccines (rotavirus 1 and rotavirus 2 vaccines) in order to be fully protected against these diseases. However, recent report from the 2014 Ghana Demographic and Health Survey (GDHS) states that, there has been a fall in immunization coverage for children aged [12][13][14][15][16][17][18][19][20][21][22][23] , it was imperative that a study is conducted to investigate the factors that determine the demand for the subsequent doses of the pneumococcal and the rotavirus vaccines among children in Ghana. Thus, helping in bringing out the factors that affect the uptake of the subsequent doses of these vaccines for children less than five years of age in Ghana, which would help in churning out policies that would aid in reducing the mortality of children in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…Immunization can reduce children mortality rate by 2.5 million per year in low and middleincome countries (Lakew et al, 2015).…”
Section: Known As Complete Basic Immunization (Idl)mentioning
confidence: 99%